2018
DOI: 10.31557/apjcp.2018.19.12.3457
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Properties of the Persian Version of the Sibling Cancer Needs Instrument (SCNI)

Abstract: The sibling cancer needs instrument (SCNI) is the first developed specifically for assessing psychosocial unmet needs of adolescents having a sibling with cancer. The aim of this study is to evaluate the psychometric properties of its Persian version. Methods: For this methodological study, the SCNI was translated into Persian using back-translation and revised according to the comments of the developer of the instrument. Then face validity, content validity, construct validity, internal consistency and the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Therefore, the level of needs decreases. Of course, it can be said that this finding is related to cultural issues (Rassouli and Sajjadi, 2014;Khanali Mojen et al, 2018;Masoudifar et al, 2018).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Therefore, the level of needs decreases. Of course, it can be said that this finding is related to cultural issues (Rassouli and Sajjadi, 2014;Khanali Mojen et al, 2018;Masoudifar et al, 2018).…”
Section: Discussionmentioning
confidence: 97%
“…The main question of the research was to estimate the mean summary PSN therefore Two pilot study was used as a sample to calculate the sample size ( Masoudifar et al, 2018 ; Ghofrani et al, 2019 ). Sample size was calculated with a confidence interval of 0.95, α = .05 z = 1.96, d = 1, and σ = 6.5 Accordingly, the sample size calculation formula ( showed that 163 participants were needed.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations